Fabricating a PDA-Liposome Dual-Film Coated Hollow Mesoporous Silica Nanoplatform for Chemo-Photothermal Synergistic Antitumor Therapy - Fan, Chuanyong; Wang, Xiyu; Wang, Yuwen; Xi, Ziyue; Wang, Yuxin; Zhu, Shuang; Wang, Miao; Xu, Lu (Pharmaceutics, 2023)
In this study, we synthesized hollow mesoporous silica nanoparticles (HMSNs) coated with polydopamine (PDA) and a D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS)-modified hybrid lipid membrane (denoted as HMSNs-PDA@liposome-TPGS) to load doxorubicin (DOX), which achieved the integration of chemotherapy and photothermal therapy (PTT). Dynamic light scattering (DLS), transmission electron microscopy (TEM), N2 adsorption/desorption, Fourier transform infrared spectrometry (FT-IR), and small-angle X-ray scattering (SAXS) were used to show the successful fabrication of the nanocarrier. Simultaneously, in vitro drug release experiments showed the pH/NIR-laser-triggered DOX release profiles, which could enhance the synergistic therapeutic anticancer effect. Hemolysis tests, non-specific protein adsorption tests, and in vivo pharmacokinetics studies exhibited that the HMSNs-PDA@liposome-TPGS had a prolonged blood circulation time and greater hemocompatibility compared with HMSNs-PDA. Cellular uptake experiments demonstrated that HMSNs-PDA@liposome-TPGS had a high cellular uptake efficiency. In vitro and in vivo antitumor efficiency evaluations showed that the HMSNs-PDA@liposome-TPGS + NIR group had a desirable inhibitory activity on tumor growth. In conclusion, HMSNs-PDA@liposome-TPGS successfully achieved the synergistic combination of chemotherapy and photothermal therapy, and is expected to become one of the candidates for the combination of photothermal therapy and chemotherapy antitumor strategies.